A gamified augmented reality vocational training program for adults with intellectual and developmental disabilities: A pilot study on acceptability and effectiveness - Tan, Bhing-Leet; Guan, Frank Yunqing; Leung, Ivy Mun Wah; Kee, Sharon Yi-May; Devilly, Oran Zane; Medalia, Alice (Frontiers in Psychiatry, 2022)
Objectives The Augmented Reality Games to Enhance Vocational Ability of Patients (REAP) was an augmented reality vocational training program that provided skills training in the context of a psychiatric rehabilitation program. It was implemented over ten weeks and consisted of gamified augmented reality café training scenarios and bridging group activities to facilitate transfer of learning to the work context. This pilot study aimed to explore the acceptability and effectiveness of the REAP program when carried out with adults with intellectual and developmental disabilities attending work therapy. Its objectives were: 1) to obtain feedback from participants and trainers on their experiences and acceptability of the REAP program and 2) to measure changes in vocational and cognitive skills of participants in the REAP program. Methods This was a pretest–posttest mixed methods study. 15 adults with intellectual and developmental disabilities attending work therapy in a non-profit organization participated in the REAP program and their vocational trainers were involved in assisting in this program. Feasibility Evaluation Checklist (FEC) and the Neurobehavioral Cognitive Status Exam (Cognistat) were administered at baseline, post-training and eight weeks after training. The participants and their trainers also provided user feedback via semi-structured interviews. Results Majority of the participants and trainers found the REAP program to be useful and interesting. They also found that the augmented reality games were user-friendly and provided a unique opportunity to acquire new skills. Participants who engaged in this program showed a significant improvement in vocational skills and aspects of cognitive skills, which were maintained eight weeks after training. Conclusion The gamified augmented reality vocational training was feasible and accepted by both adults with intellectual and developmental disabilities and their trainers. When integrated with bridging sessions to facilitate transfer of learning to existing work therapy, participants on the REAP program showed significant improvements in vocational skills and aspects of cognitive skills. Future experimental studies with larger sample size could provide stronger evidence on its effectiveness in improving vocational outcomes.